Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPS menggunakan Metode Picture and Picture Kelas III SDN-1 Kasongan Lama Tahun Pelajaran 2016/2017: Efforts to Improve Student Learning Outcomes in Social Sciences Subjects using the Picture and Picture Method Class III SDN-1 Kasongan Old 2016/2017 Academic Year - Nova Karlina; Ichyatul Afrom (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the activity and improvement of student learning outcomes in social studies learning on material types - types of work by using the picture and picture method in class III SDN-1 Kasongan Lama. The technique used in this study is the Classroom Action Research (CAR) ) with the research subjects of all class III students totaling 20 people. The data analysis technique uses qualitative and quantitative analysis based on the results of the cycle in each learning process. The results of the study show that: (1) The activities of students during the social studies learning process using the picture and picture method in class III SDN - 1 Kasongan Lama are more active. This is evidenced by the results of the average activity of students in the first cycle, namely 3.3 which included the category (right) and the effects of the average activity of the teacher in the first cycle obtained a value of 3.4 which included the group (right); (2) there is an increase in social studies learning outcomes of students after the learning process using the picture and picture method for students in class III of the Kasongan Lama Elementary School. This is evidenced by the learning outcomes of students in the first cycle obtained an average value of 80 with the percentage of completeness of classical learning outcomes reached 90%.